The contribution of collagen fibers to the mechanical compressive properties of the temporomandibular joint disc. Issue 7 (July 2016) - Fazaeli, S.; Ghazanfari, S.; Everts, V.; Smit, T.H.; Koolstra, J.H.
Summary: Objective: The Temporomandibular Joint (TMJ) disc is a fibrocartilaginous structure located between the mandibular condyle and the temporal bone, facilitating smooth movements of the jaw. The load-bearing properties of its anisotropic collagenous network have been well characterized under tensile loading conditions. However, recently it has also been speculated that the collagen fibers may contribute dominantly in reinforcing the disc under compression. Therefore, in this study, the structural-functional role of collagen fibers in mechanical compressive properties of TMJ disc was investigated. Design: Intact porcine TMJ discs were enzymatically digested with collagenase to disrupt the collagenous network of the cartilage. The digested and non-digested articular discs were analyzed mechanically, biochemically and histologically in five various regions. These tests included: (1) cyclic compression tests, (2) biochemical quantification of collagen and glycosaminoglycan (GAG) content and (3) visualization of collagen fibers' alignment by polarized light microscopy (PLM). Results: The instantaneous compressive moduli of the articular discs were reduced by as much as 50–90% depending on the region after the collagenase treatment. The energy dissipation properties of the digested discs showed a similar tendency. Biochemical analysis of the digested samples demonstrated an average of 14% and 35% loss in collagen and GAG, respectively. Despite the low reduction of collagen content the PLM images showed considerable perturbation of the collagenous network of the TMJ disc. Conclusions: The results indicated that even mild disruption of collagen fibers can lead to substantial mechanical softening of TMJ disc undermining its reinforcement and mechanical stability under compression.